Serum thiamine concentration and oxidative stress as predictors of mortality in patients with septic shock - Costa, Nara Aline [UNESP]; Gut, Ana Lúcia [UNESP]; Dorna, Mariana de Souza [UNESP]; Coelho Pimentel, Jose Alexandre; Franciscato Cozzolino, Silvia Maria; Gaiolla, Paula Schmidt Azevedo [UNESP]; Fernandes, Ana Angelica Henrique [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Minicucci, Marcos Ferreira [UNESP] (Elsevier B.V., 2014)
Purpose: The purpose of the study is to determine the influence of serum thiamine, glutathione peroxidase (GPx) activity, and serum protein carbonyl concentrations in hospital mortality in patients with septic shock.Materials and Methods: This prospective study included all patients with septic shock on admission or during intensive care unit (ICU) stay, older than 18 years, admitted to 1 of the 3 ICUs of the Botucatu Medical School, from January to August 2012. Demographic information, clinical evaluation, and blood sample were taken within the first 72 hours of the patient's admission or within 72 hours after septic shock diagnosis for serum thiamine, GPx activity, and protein carbonyl determination.Results: One hundred eight consecutive patients were evaluated. The mean age was 57.5 +/- 16.0 years, 63% were male, 54.6% died in the ICU, and 71.3% had thiamine deficiency. Thiamine was not associated with oxidative stress. Neither vitamin B1 levels nor the GPx activity was associated with outcomes in these patients. However, protein carbonyl concentration was associated with increased mortality.Conclusions: In patients with septic shock, oxidative stress was associated with mortality. On the other hand, thiamine was not associated with oxidative stress or mortality in these patients. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Septic shock; Glutathione peroxidase; Mortality; Thiamine; Protein carbonyl